Extreme weather events cause significant crop yield losses at the farm level in German agriculture. (October 2022) - Schmitt, Jonas; Offermann, Frank; Söder, Mareike; Frühauf, Cathleen; Finger, Robert
Highlights: We estimate economic effects of extreme weather events on crop yields in Germany. We combine 423, 815 observations of farm-level yields with weather, crop-specific soil moisture and phenology. Drought is the most relevant climate extreme in German crop production. Average annual losses due to drought in winter wheat alone exceed 23 million Euros. Drought effects became more relevant in the recent past. Results provide policy makers with empirical insights to regionally prioritize the support of weather risk management and adaptation measures and assess their respective public costs. Abstract: Extreme weather events frequently cause severe crop yield losses, affecting food security and farmers' incomes. In this paper, we aim to provide a holistic assessment of these impacts across various extreme weather events and multiple crops. More specifically, we estimate and compare the impact of frost, heat, drought and waterlogging on yields of winter wheat, winter barley, winter rapeseed and grain maize production in Germany. We analyse 423, 815 farm-level yield observations between 1995 and 2019, and account for extreme weather conditions within critical phenological phases. Furthermore, we monetarize historical yield losses due to extreme weather events on a spatially disaggregated level. We find that drought is a main driver for farm-level grain yield and monetary losses in German agriculture. For instance, a single drought day can reduce winter wheat yields by up to 0.36%. It is estimated that during the period 1995–2019, summer drought led to yield losses in winter wheat, which, on average, caused annual revenues to sink by over 23 million Euro across Germany. We find that the impacts of extreme weather events vary considerably across space and time. For example, only the most important winter rapeseed production region in the North of Germany was prone to winter rapeseed yield losses due to heat during flowering. Moreover, waterlogging and frost are generally less relevant from an economic point of view, but can nevertheless cause crop- and regional-specific damage. Our analysis provides stakeholders with information for weather-related risk management and adaptation strategies.